GABs: A Game-Based Secure and Energy Efficient Data Aggregation for Wireless Sensor Networks - Tristan Daladier Engouang; Yun Liu; Zhenjiang Zhang (International Journal of Distributed Sensor Networks)
This paper endeavors to investigate the security and energy issues in wireless sensor networks from prior art such as game theory and various embodiments of methods like public-key cryptography. Due to the needs of interacting with the physical world, thanks to a plethora of innovative applications, the state of the art in wireless sensor networks (WSNs) is focusing on multiple purposes such as monitoring, tracking, and security while relying upon some assumptions about distributed data, whereas these assumptions may not hold in a real scenario. The content herein models homogeneous WSN environment of highly linked nodes, in a theoretical game with synchronized actions, where, in order to transmit their readings securely across the network in some level of hierarchy, using the technique of data aggregation, sensor nodes with communication and computational resources constraint should establish trusted and direct links between their neighbors for the privacy and integrity of their data against faulty nodes, while ensuring energy saving. The study considers the ZigBee known as IEEE 802.15.4 standard for its high trustworthiness and low power consumption in wireless sensor network and compares different topology models.